Electrochemical monitoring of the degradation of galvanized steel in simulated marine atmosphere. (February 2019) - Liu, Y.; Ooi, A.; Tada, E.; Nishikata, A.
Highlights: The degradation stages of electro-galvanized steel were clearly distinguished by EIS, a non-destructive method. The very stage with corrosion protection by zinc corrosion products was monitored by EIS. Understanding such stage is critical to define the service life of galvanized coatings. Different thicknesses of electro-galvanized coatings confirmed reproducibility. Abstract: Galvanized steels with different thicknesses of coatings were exposed to the wet–dry cycles in the presence of NaCl. The degradation of galvanized steels was investigated at different exposure times by electrochemical impedance spectroscopy. Further, the degradation is categorized into four characteristic stages, including τ1 : dissolution of zinc, τ2 : galvanic protection by metallic zinc, τ3 : barrier protection by zinc corrosion products, and τ4 : onset of the underlying steel corrosion, respectively. The underlying steel was protected by the zinc corrosion products for a relatively long time even after the metallic zinc coating was completely corroded (i.e., the τ3 stage).